2024
DOI: 10.1037/dhe0000388
|View full text |Cite
|
Sign up to set email alerts
|

“Failing to respond”: Black graduate students’ perceptions of a university president’s responses to racialized incidents.

Abstract: Guided by Hurtado et al.'s (2012) Multi-Contextual Model for Diverse Learning Environments, this qualitative case study examined Black graduate students' perceptions of a university president's responses to racialized incidents. Data were analyzed on an institutional level through institutional documents and presidential statements and individually through interviews with 12 Black graduate students from the University of Maryland, College Park. The findings were displayed through narrative summaries and demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 51 publications
(144 reference statements)
1
11
0
Order By: Relevance
“…Furthermore, while students acknowledged that some faculty and administrators engaged in dialogues about campus history after the rallies, most of these conversations failed to translate into veritable action. This is consistent with other evidence that institutions use official statements from senior-level administrators to ease negative publicity without concomitant attention to measurable change (Briscoe, 2022). Given the power and privilege within positions of university leadership (i.e., the president, the executive board, and deans and provosts), their commitment and collaboration around institutional antiracism are essential for campus change (Arellano & Vue, 2019; Kezar, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, while students acknowledged that some faculty and administrators engaged in dialogues about campus history after the rallies, most of these conversations failed to translate into veritable action. This is consistent with other evidence that institutions use official statements from senior-level administrators to ease negative publicity without concomitant attention to measurable change (Briscoe, 2022). Given the power and privilege within positions of university leadership (i.e., the president, the executive board, and deans and provosts), their commitment and collaboration around institutional antiracism are essential for campus change (Arellano & Vue, 2019; Kezar, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…Overall, our findings point to an undeniable need for the deconstruction of socialization to reimagine more inclusive practices along the doctoral journey. Indeed, Black graduate students have experienced chilly hostile racial climates (Briscoe, 2022(Briscoe, , 2023a(Briscoe, , 2023bK. A. Griffin et al, 2012;Slay et al, 2019); however, Black women doctoral students specifically have had arduous doctoral experiences (Grant, 2021;C.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Cole and Harper (2017) found that through their response statements to racist incidents, presidents often addressed the broader campus community in generic ways rather than the individuals directly impacted. In addition, when administrators respond to racialized incidents, they often approach racism as an individual act blamed on the perpetrator, failing to acknowledge the presence of systemic racism on their campus (Briscoe, 2022). This ability to control institutional narratives through rhetoric has significance because when administrators emphasize the value of dominant ideals such as free speech over condemning racism, they may reinforce white ideologies (Jones, 2019).…”
Section: Teaching As a Political Act: Faculty Members Use Of Critical...mentioning
confidence: 99%